(3OjhGf GdJgGeis - (3Ydj Hf eMeO Hf agO, CHh GdMSf GdJgGej,J (B416 (3g` s
(3ChdgG (B:s
(3CQMJ faSi ef YdGI GdedGM ddjCS QhM eKd QhM GdfLGM s
(3BNQgG (B:s
(3ZjKG jWHb ai GdhgGO bjSJhi ai GdYjf efXQ CQLg hSeGg s
(3dYd GdOjhGf HYV ef GdeNJGQGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B145 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B219s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI HgG CQVg s
Keywords: (3GdCOHs